Twitter Campaigning Strategies in Australian Federal Elections 2013–2019. (December 2021) - Bruns, Axel; Angus, Daniel; Graham, Timothy
This special issue of Social Media + Society develops a cross-national, longitudinal perspective on the use of social media in election campaigns. Australia, where leading social media platforms such as Facebook and Twitter were adopted early and widely by the general population, and where federal election cycles are unusually short (often less than 3 years), provides a particularly suitable environment for observing the evolution of social media campaigning approaches. This article extends our analysis of previous federal election campaigns in Australia by examining Twitter campaigning in the 2019 election; to allow for a direct comparison with previous campaigns, it builds on a methodological and analytical framework that we have used since the 2013 election.